Lone Star tarnished : a critical look at Texas politics and public policy - Jillson, Calvin C., 1949- (Routledge, 2025)
Texas pride, like everything else in the state, is larger than life. So, too, perhaps, are the state's challenges. Lone Star Tarnished approaches public policy in the nation's most populous "red state" from historical, comparative, and critical perspectives. The historical perspective provides the scope for asking how various policy domains have developed in Texas history.In each chapter, Cal Jillson compares Texas public policy choices and results with those of other states and the United States in general. Finally, the critical perspective allows readers to question the balance of benefits and costs attendant to what is often referred to as "the Texas way" or "the Texas model" and to assess the many claims of Texas's exceptionalism.Through Jillson's lively and lucid prose, students are well equipped to analyse how Texas has done and is doing compared to selected states and the national average over time and today. This text is aimed at students and professors of Texas politics who want to stress history, political culture, and public policy.New to the Fifth Edition Fully updated to include the most recent Texas elections and political events Covers the 2023 legislative session Highlights new population data, with projections forward to 2050, recently released by the U.S. Census and the Texas State Data Center Explores the dramatic increases in Texas oil and gas production and their impact on global and U.S. prices and on the profitability and the viability of many Texas producers in light of the recent plunge in prices All figures and tables include the most recent data available